Changes in the concept designated by the term mariage civil throughout the history of French law 1791–2013 - Curti-Contessoto, Beatriz; de Oliveira, Isabelle; Barros, Lidia Almeida [UNESP] (John Benjamins Publishing Company, 2021)
In 1791, the term mariage civil first appeared in French law in order to designate a civil and secular union recognised only by the State. After the introduction of this term into the French legal domain, there were legislative changes regarding the rules of civil marriages over the following years. The present paper examines the semantic evolution of the term mariage civil in French law, relating this evolution to socio-cultural and historical aspects of France between 1791 (when civil marriage was instituted in this country) and 2013 (when the most recent legislative change in the area occurred). Based on this investigation, it is possible to affirm the transformations in the French society and legislative changes have modified the concept designated by the term mariage civil, especially concerning the notion of family and the achievement of rights by women and homosexuals.
Keywords: Civil marriage; Diachronic terminology; Legal domain; Legal language; Legislative changes; Semantic evolution